Effects of Biochar Application on Enzyme Activities in Tea Garden Soil - Jiang, Yunli; Wang, Xiangjun; Zhao, Yaming; Zhang, Changai; Jin, Zewen; Shan, Shengdao; Ping, Lifeng (Frontiers in Bioengineering and Biotechnology, 2021)
Animal-manure biochar used as sustainable amendment to garden soil has been widely applied, and the animal-manure pyrolysis temperatures would also have a regulatory effect on soil functions because of their affections on biochar physio-chemical properties. Here we studied the effects of different dosages of swine-manure biochar on tea garden soil functions, with the swine-manure pyrolysis temperature differed at 350 ℃ and 500 ℃. The results showed that the improvement of soil microbial biomass carbon and nitrogen, and enzyme activities were closely related to the addition of 0.5%-2% (biochar wt/soil wt) swine-manure biochar. Under different conditions of different carbon application rates and carbon type, the addition of 2% swine-manure biochar pyrolysed at 350 ℃ showed the best effects on soil enzyme activities and microbial biomass carbon and nitrogen contents. Compared to the control, after the addition of 2% swine-manure biochar, sucrase, phosphatase, catalase, and urease activities increased by 63.3%, 23.2%, 50.3%, and 27.9%, respectively. Microbial biomass carbon and nitrogen contents also increased by 36.4% and 34.3%, respectively. Our study indicated that the effectiveness of using animal-manure swine-manure biochar as sustainable amendment to soil, which would provide evidences of tea garden soil improvement and the environmental response to the usage of biochars.